Beware the ides of Morel-Lavallée: A lesion to consider when diagnosing trauma patients - John Wahhab; Andrew Zwijack (Trauma Case Reports, 2023)
Morel-Lavallée lesions are post-traumatic, internal degloving injuries associated with substantial patient mortality that are frequently undetected due to often presenting days to weeks after initial injury. Delay of diagnosis can perpetuate complications such as expansion and infection (Mutluoglu et al., 2021 [1]). A 46 year old male presented with a Morel-Lavallée lesion to the left anterior thigh and hip two weeks after receiving emergency care after an accident where he was thrown from his motorcycle. It is paramount that physicians consider this diagnosis when evaluating post-traumatic patients to mitigate lesion expansion, overlying skin necrosis, underlying fracture exposure and subsequent infection.